The role played by Leonard Cheshire Disability Zimbabwe Trust in promoting inclusive education for the disabled children in Murehwa (2010 to 2013) - Muzambi, Nyasha Karen (Midlands State University, 2015)
Education for disabled children has for years been taken for granted with societies wanting disabled persons to fit into the society without the society changing. This research was carried out in Murehwa with the main aim of examining the role played by LCDZT in promoting inclusive education for children with disabilities. The objectives of the study included analyzing the benefits of inclusive education for CWDs, examining the importance of implementing inclusive education, exploring the current situation of inclusive education in Murehwa and looking at the challenges that were faced by inclusive education. In the bid to fulfill these objectives literature was reviewed and a descriptive research was conducted. 35 questionnaires were administered to people who are somehow related to disability and 10 people were also interviewed. The researcher found out that LCDZT played an enormous role in promoting inclusive education which in the program implementation process has changed the perception of people as well as their approach to disability from an integrated approach to a more accommodating twin track approach which encourages the full participation of disabled persons